2018
DOI: 10.1186/s13071-018-3001-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in the adulticidal efficacy of essential oils for the improvement of permethrin toxicity against Aedes aegypti L. (Diptera: Culicidae)

Abstract: BackgroundIn a previous screening program for mosquitocides from local edible plants in Thailand, essential oils (EOs) of Cyperus rotundus, Alpinia galanga and Cinnamomum verum, were found to possess promising adulticidal activity against Aedes aegypti. With the aim of reducing usage of conventional insecticides and improving the management of resistant mosquito populations, this study was designed to determine the potential synergism in the adulticidal efficacy of EOs on permethrin toxicity against Ae. aegypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…ANOVA F 5,14 5.42** 2 9.03** 7.32** 2 17.98** 37.57** 2 311.1** against Ae. aegypti, including an insecticide-resistant strain (Chansang et al 2018). Similarly, Norris et al (2018) reported that oils of geranium, oregano, and patchouli, as well as others, synergized permethrin against insecticide-resistant Ae.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…ANOVA F 5,14 5.42** 2 9.03** 7.32** 2 17.98** 37.57** 2 311.1** against Ae. aegypti, including an insecticide-resistant strain (Chansang et al 2018). Similarly, Norris et al (2018) reported that oils of geranium, oregano, and patchouli, as well as others, synergized permethrin against insecticide-resistant Ae.…”
Section: Resultsmentioning
confidence: 93%
“…Oils of rhyzae of purple nutsedge ( Cyperus rotundus ) and galangal ( Alpinia galanga ) synergized permethrin against Ae. aegypti , including an insecticide‐resistant strain (Chansang et al ). Similarly, Norris et al () reported that oils of geranium, oregano, and patchouli, as well as others, synergized permethrin against insecticide‐resistant Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of C. cyminum has been extensively explored for its antioxidant and antimicrobial activities [92,93], but most of the investigations focused only on the bioactivities of the essential oil and have seldom considered what is the most responsible component for its specific bioactivity. Although synergy was a popular account of the essential oil bioactivities [94,95], overemphasizing synergy is not useful for the elucidation of the mode of these bioactivities and consequently, for the development of more effective remedies. Since the preciousness of natural-derived essential oils makes it financially unfeasible to practically use them to achieve the desired effects, the investigation of the function mechanisms of their bioactive components is of practical significance, so that some low cost alternatives can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Among the strategies adopted, most chemical insecticides attack adult mosquitoes or their larval stages. 5,7 The reduction of the mosquito population is easier in immature stages (larva or pupa). 8 Most soluble pesticides are organophosphates that inhibit the enzyme, causing paralysis and then death of larvae.…”
Section: Introductionmentioning
confidence: 99%